Validity and reliability of GPS for measuring instantaneous velocity during acceleration, deceleration, and constant motion - Varley, M. C.; Fairweather, I. A.; Aughey, R. J. (Journal of Sports Sciences, 2012)
In this study, we assessed the validity and reliability of 5 and 10 Hz global positioning systems (GPS) for measuring instantaneous velocity during acceleration, deceleration, and constant velocity while straight-line running. Three participants performed 80 running trials while wearing two GPS units each (5 Hz, V2.0 and 10 Hz, V4.0; MinimaxX, Catapult Innovations, Scoresby, VIC, Australia). The criterion measure used to assess GPS validity was instantaneous velocity recorded using a tripod-mounted laser. Validity was established using the standard error of the estimate (±90% confidence limits). Reliability was determined using typical error (±90% confidence limits, expressed as coefficient of variation) and Pearson's correlation. The 10 Hz GPS devices were two to three times more accurate than the 5 Hz devices when compared with a criterion value for instantaneous velocity during tasks completed at a range of velocities (coefficient of variation 3.1-11.3%). Similarly, the 10 Hz GPS units were up to six-fold more reliable for measuring instantaneous velocity than the 5 Hz units (coefficient of variation 1.9-6.0%). Newer GPS may provide an acceptable tool for the measurement of constant velocity, acceleration, and deceleration during straight-line running and have sufficient sensitivity for detecting changes in performance in team sport. However, researchers must account for the inherent match-to-match variation reported when using these devices.